Movilidad espacial de la población y cambios recientes del modelo de densidad en ciudades del sistema urbano chileno - Escolano Utrilla, Severino; Ortiz Véliz, Jorge (Geographicalia, 2016)
This paper deals with some changes that recently have taken place in the density population model of some cities belonging to the Chilean urban system. The main features of the new model, compare with the previous compact city one, are: fragmentation in several parts, reorganization around many spatial modes and density average decrease. One consequence of the population redistribution in the urban space is the increase on the distance and time average between the residence places and the urban center or the functional areas.The immediate causes of the population distribution model restructuring are found in the fragmentation of the urban builts space and in the successive intraurban migration waves, which predominant direction is from the center to the increasingly far away peripheries. We also state that some changes on the population density model are common to many cities and, therefore, independent to its size.
Keywords: Density of urban population; urban fragmentation; urban migrations.